PENGARUH TIPE KETERLIBATAN ENDURING KONSUMEN TERHADAP KEPERCAYAAN MEREK DAN DAMPAKNYA PADA KEPUTUSAN PEMBELIAN PRODUK SMARTPHONE - Nurhayati, Siti (PRIMA EKONOMIKA, 2020)
ABSTRACTThis study aims to determine the extent to which the type of involvement of consumerenduring on brand trust and its impact on the decision to purchase Samsung smartphoneproducts in Yogyakarta Special Region. The population of this study is Samsung smartphoneusers in Yogyakarta Special Region by using the number of samples of 200 respondents.Sampling using nonprobability sampling technique, while the technique of determining thesample using purposive sampling. The data in the study will be taken using a questionnaire.In this research, hypothesis test is done by using simple linear regression analysis, processedby using SPSS 20.0 program, it is necessary to know the influence of independent variable todependent variable. Tests of parameter values generated will be done by using t-test and testcoefficient of determination (RÂ²).The results of this study indicate that the involvement of consumer enduringsignificant effect on brand trust, brand trust effect on purchasing decisions. Brand trust has asignificant effect as an intervening variable between the variables of enduring consumerengagement and purchasing decisions. This can be seen from the adjusted value of R2 on modelI = 0.037 smaller than the value of adjusted R2 on model II = 0.084.Keywords: type of enduring engagement, brand trust, purchase decision.